CHALLENGES AND APPROACHES IN ENGLISH LANGUAGE TEACHING: A MAJOR ENIGMA IN TODAY’S ERA - Dr. Shriya; Monika; Kaur, Prabhdeep (ShodhKosh: Journal of Visual and Performing Arts, 2024)
English, a language that is widely spoken today, has frequently been referred to as a “world wide language.” The current era’s “lingua franca” is instructed and learned worldwide as a second language, because of ethnic diversity and linguistic variety. English is used in India not just as a connecting language between people of different states but for communication and for coordination between and within states. Even, if modern technology has begun to play a crucial part in language learning instruction in schools and universities, it is still insufficient and unproductive, particularly in small towns and rural areas. Children who study English in schools and at college level, pass the tests without putting ample effort to comprehend the language or acquire the ability to value its usefulness. This paper emphasizes on the paramountcy of understanding English as a means to meet the ever increasing demands of the Cutthroat Business Globe and will also examine the challenges faced by the educators in Modern English language Teaching and solutions to these challenges.